2020
DOI: 10.1038/s41598-020-60478-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence trends of airflow obstruction among European adults without asthma: a 20-year cohort study

Abstract: Investigating COPD trends may help healthcare providers to forecast future disease burden. We estimated sex-and smoking-specific incidence trends of pre-bronchodilator airflow obstruction (AO) among adults without asthma from 11 European countries within a 20-year follow-up (ECRHS and SAPALDIA cohorts). We also quantified the extent of misclassification in the definition based on prebronchodilator spirometry (using post-bronchodilator measurements from a subsample of subjects) and we used this information to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Importantly, AFO has been found to be a critical element of certain diseases, such as chronic obstructive pulmonary disease (COPD) (2). Among individuals with AFO, 43%-74% are COPD patients (3)(4)(5), and COPD has become a major public health problem in China (6). The aim of this study was thus to estimate the level and characteristics of lung function and AFO in a sample population of adults living in Beijing in order to better serve populations such as those suffering from COPD.…”
Section: What Is Added By This Report?mentioning
confidence: 99%
“…Importantly, AFO has been found to be a critical element of certain diseases, such as chronic obstructive pulmonary disease (COPD) (2). Among individuals with AFO, 43%-74% are COPD patients (3)(4)(5), and COPD has become a major public health problem in China (6). The aim of this study was thus to estimate the level and characteristics of lung function and AFO in a sample population of adults living in Beijing in order to better serve populations such as those suffering from COPD.…”
Section: What Is Added By This Report?mentioning
confidence: 99%
“…Some centres had other equipment, but these differences are not believed to have affected the homogeneity of the results. 29 The type of spirometer used at each centre has been presented by Accordini et al 30 Spirometry measurements were performed with the study person in a sitting position, wearing a nose clip, and in accordance with the instructions of the American Thoracic Society (ATS)/European Respiratory Society (ERS). 31 All spirometry tests fulfilled the ATS data collection standards regarding validity of measurements, ie, 5 or more acceptable spirometry performances.…”
Section: Lung Functionmentioning
confidence: 99%
“…Exercise therapy (ET) is a therapeutic form of training that improves the body’s exercise endurance and improves cardiopulmonary function. Many studies have proved that aerobic exercise is an effective way to improve systemic inflammation ( Accordini et al, 2020 ), in particular, has a good effect on improving lung function and exercise ability, and reducing systemic inflammation in COPD patients ( Wen et al, 2019 ). Braz Júnior et al (2015) found that whole-body vibration (WBV) was effective in improving the 6-min walk distance (6MWD) ability of COPD patients with a good positive modulating effect on the quality of life assessed by the St. George’s Respiratory Questionnaire (SGRQ).…”
Section: Introductionmentioning
confidence: 99%